Pengembangan Diri Mahasiswa melalui Organisasi Kemahasiswaan (Indo-MathEdu Intellectuals Journal, 2026)
This study is a systematic literature review that aims to analyze the role of student organizations in students' self-development, particularly in the areas of soft skills, leadership, and professional readiness. The background of this study is the gap between the competencies of university graduates and the evolving demands of the labor market. The method used is a Systematic Literature Review (SLR), drawing data from 27 national journal articles indexed in Sinta 2–4 and retrieved through Google Scholar, Portal Garuda, and the Sinta database, which were then analyzed through thematic synthesis across the identified studies. The findings indicate that student organizations consistently serve as effective non-formal learning environments. Three main dimensions are influenced: first, the development of soft skills, including communication, leadership, and conflict management; second, the enhancement of interpersonal intelligence and social skills; and third, the improvement of students' professional readiness. This study is limited by its reliance on secondary literature without primary empirical verification, so longitudinal and experimental research is recommended to confirm the causal impact of organizational involvement. These findings imply the need to integrate organizational experiences as a component of holistic competency assessment within Indonesia’s higher education system